2017
DOI: 10.1016/j.whi.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Problem Drinking among Women Firefighters

Abstract: Objectives Given high levels of occupational stress and toxic exposures, firefighters have a relatively high prevalence of occupationally-related medical and mental health disorders compared to the general public. Previous research found high rates of heavy and binge drinking among male firefighters. This study is the first to examine alcohol use among women firefighters. Methods Data were collected as part of a national online survey of women, career firefighters. Results A total of 1,913 women firefighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 42 publications
(61 reference statements)
1
30
1
5
Order By: Relevance
“…Recruitment strategies are more specifically outlined in previous publications [23, 24] but included recruitment through contacts with previous participants, emails from organizations (e.g., iWomen, International Association of Firefighters), listserves (e.g., www.firefighterclosecalls.com), and through social media postings. Secondary recruitment included requesting any women who completed the survey to share the solicitation with their women colleagues.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recruitment strategies are more specifically outlined in previous publications [23, 24] but included recruitment through contacts with previous participants, emails from organizations (e.g., iWomen, International Association of Firefighters), listserves (e.g., www.firefighterclosecalls.com), and through social media postings. Secondary recruitment included requesting any women who completed the survey to share the solicitation with their women colleagues.…”
Section: Methodsmentioning
confidence: 99%
“…This study and its protocols were approved by the Institutional Review Board (IRB) of the National Development and Research Institutes, Inc. Details about the survey protocol and consent can be found in Jahnke et al [23] and Haddock and colleagues [24]. This survey focused on women in the career fire service specifically rather than including volunteers as career firefighters are exposed to the greatest risk, are more active responding to calls, and spend more time in the culture of the firehouse [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, firefighters with PTSD symptoms may be at heightened risk for the development of AUD due to coping-motivated alcohol use (Bacharach et al, 2008;Zegel et al, 2019). Emerging work has established high rates of PTSD and AUD in the fire service (Arbona & Schwartz, 2016;Bing-Canar et al, 2019;Haddock et al, 2015Haddock et al, , 2017Tomaka et al, 2017), highlighting the need for effective treatments among firefighter populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite a growing body of research for male health in fire services, currently there is limited work on the specific health needs of women (Jahnke et al, 2012;Sinden et al, 2013). Within the WFF population previous research has identified high alcohol intakes (Haddock, Poston, Jahnke, & Jitnarin, 2017), high rates of depression (Centers for Disease Control and Prevention, 2010), anxiety, post-traumatic stress disorder (PTSD) and suicide (Stanley, Hom, Spencer-Thomas, & Joiner, 2017), as well as pregnancy complications (Jahnke, Poston, Jitnarin, & Haddock, 2018). Most published women specific research originates from the USA and to our knowledge there is no documentation on women's perspectives of health and wellbeing needs, particularly surrounding gynaecological health.…”
Section: Introductionmentioning
confidence: 99%